Lateral force-displacement response of rat-trap bonded masonry. (1st April 2022) - Samiullah,; Ashraf, Mohammad; Fahim, Muhammad; Haris, Muhammad; Badshah, Eid
Abstract: Rat-trap bond (RTB) masonry is one of the most economical, fast, and energy efficient construction technique for brick masonry buildings. Many developing countries including India, Nepal, Sri Lanka and Pakistan have constructed large number of buildings using this technique. However, structural stability and performance validation are as important as the economy in any construction project. Therefore, this study presents the results of in-plane quasi-static cyclic load tests on three wall specimens constructed in RTB. The pre-compression load was adjusted to simulate the load condition of a typical two storey building. The key parameters evaluated include stiffness, ductility, damping, energy dissipation, force-displacement behaviour, lateral strength, etc. The experimentally obtained results were also compared with the existing research of similar nature on conventional masonry as well as with the results predicted by various empirical equations. The comparison indicates that the lateral strength and stiffness of rat-trap masonry is significantly less than those of conventional masonry because of the reduced effective thickness, while other properties like ductility, damping and energy dissipation do not show any significant variation. Highlights: Rat-trap bond (RTB) masonry is one of the most economical, fast, and energy efficient construction technique. Rat-trap bond (RTB) masonry subjected to in-plane quasi-static cyclic load tests. Lateral strength and stiffness of rat-trap masonry is significantly less than those of conventional masonry. RTB has good energy dissipation capacity as obvious from the wider hysteresis loops. The compressive strength of RTB masonry prism is significantly greater than those reported in literature.